Pengetahuan, sikap, dan tindakan masyarakat tentang malaria di Lingkungan VI Kelurahan Taas Kecamatan Tikala Kota Manado - Athalia, Zelda Fitri; Rombot, Dina Victoria; Monintja , Tyrsa Christine Natalia (UNIVERSITAS SAM RATULANGI, 2023)
Background: Until now, malaria has become an infectious disease and a global health problem, including in Indonesia. Factors such as community knowledge, attitudes, and actions have an important role in the incidence of malaria. Based on data from the Tikala Baru Primary Health Center, during the period January 2023 to August 2023, 6 cases of malaria were recorded, of which 3 cases came from Neighborhood VI of Taas Village. Aim: To assess the knowledge, attitudes, and practice of the community towards malaria. Methods: The method used was descriptive analytic with a cross-sectional approach. Data analysis was conducted through a univariate analysis approach.Results: This study included 90 respondents as samples. The level of knowledge of respondents in Neighborhood VI of Taas Village was classified in the good category (72%), the attitude of the community was positive (100%), and the level of action was moderate (50%).Conclusion: Respondents in Neighborhood VI of Taas Village had good knowledge, positive attitudes, and moderate actions.Keywords: malaria, knowledge, attitude, practice, neighborhood VI, Taas Village